The Bobaths’ approach to Cerebral Palsy habilitation - a review - Saraswathi Menon (Journal of All India Institute of Speech and Hearing, 1970)
The Bobaths’ method of treatment (Bobath and Bobath 1955,1959) of cerebral palsy is one of physiological rehabilitation and is based upon resistance to primitive reflex patterns that children with this problem tend to exhibit. Their approach differs from other approaches currently practiced and is based on the premise that the fundamental disturbance in the motor behavior of the cerebral palsied child is his inability to inhibit control over basic postural reflexes. Their treatment enables the patient to achieve control over the larger muscular movements required for moving his body, which the Bobaths feel, is a prerequisite for gaining control over the finer movements required for speech.